JPHD Instructions for Contributors (Journal of Public Health Dentistry, 2006)
Objective The study aimed to determine the key factors that predict oral health care utilization among persons with and without depression. Methods Data from 17,525 working-age adults from the 2022 National Health Interview Survey were analyzed. Survey-weighted Poisson regression models estimated the population-level associations between sociodemographic factors (e.g., income, education, last medical visit) and a report of no past-year dental visit and Delayed Dental Care due to cost (DDC), while Random Forest (RF) permutation importance quantified each variable's contribution to predictive discrimination for individuals with or without depression. Results The adjusted prevalence (aPR) of no past-year dental visit and DDC was greater among those with depression compared to those without depression (39.6% vs. 35.3% aPR = 1.12; 95% confidence interval (CI), 1.06 to 1.18) and (26.6% vs. 17.8%, aPR = 1.47, 95% CI, 1.35, 1.59), respectively. Our RF models demonstrated an acceptable range of discrimination for both outcomes (AUC range: 0.67-0.73) across the subgroups by depression status. Income was the most important variable contributing most to all four models' discrimination, regardless of depression status, suggesting a cross-cutting impact on oral health service utilization regardless of depression status. Conclusion Individuals with depression were less likely to visit the dentist and more likely to report cost-related delayed dental care than those without depression. Further, income was an important factor impacting oral health care-seeking behavior.